An enhanced recovery programme after caesarean delivery increases maternal satisfaction and improves maternal-neonatal bonding: A case control study. (March 2017) - Laronche, Anne; Popescu, Luiza; Benhamou, Dan
Abstract: Objectives: Enhanced recovery programmes (ERP) have been shown to improve postoperative outcomes. The aim of our study was to investigate the impact of an ERP after caesarean delivery on maternal feelings and satisfaction towards mother-child bonding initiation, in comparison with traditional postoperative care. Study design: A comparative, prospective and multicentre study was conducted in three maternity units of the Paris area: one applied traditional postoperative care while the two others applied an ERP, were included patients after elective or emergency caesarean delivery who had given birth to full-term healthy singleton newborns. Data were collected from 8th October 2014 to 31st January 2015. Patients were asked about their feelings toward the relationship with their infant using a questionnaire, to be completed one (D1) and three (D3) days after caesarean delivery. Results: Patients (n = 86) received post-operative care in agreement with what was expected in the group in which they were included. Patients in the ERP group had more positive feelings toward the relationship with their newborn on D1 and D3, had a greater maternal satisfaction level on D1 and were more comfortable in caring for their newborn, especially for cradling and breastfeeding the child. Conclusion: Our study suggests that application of ERP after caesarean delivery is associated with improved maternal satisfaction and more positive feelings toward the relationship with the newborn.